A Review of the Effects and Mechanisms of VR Training on the Physical and Mental Health of Stroke Patients - Xue Mei Wu; Chuan Qiu Shui Wang; Cheng Yu Wang; Jiong Luo (International Journal of Education and Humanities, 2025)
To explore the effects of virtual reality (VR) training on the physical and mental rehabilitation of stroke (CVA) patients and its underlying mechanisms, to address issues such as monotonous training, low compliance, and limited environmental simulation in traditional rehabilitation. This study aims to provide a theoretical basis for optimizing clinical rehabilitation strategies. Databases such as PubMed (Medline), Web of Science, Cochrane Library, Google, CNKI, and Wan fang Data were used to search for literature published in core journals from both domestic and international sources over the past 10 years (2014-2024). Keywords included: virtual reality, VR training, stroke, cerebrovascular accident, physical and mental health, and mechanism of action. Inductive summarization and comparative analysis methods were applied to process the selected literature. Different VR training methods can not only improve the upper and lower limb strength and balance of stroke patients, but also significantly enhance their activities of daily living (ADL). Additionally, these training methods can alleviate anxiety and improve depression and other psychological issues in stroke patients. The improvement in physical and mental health due to VR training may be achieved through a synergistic effect of neuroplasticity and psychological immersion. VR training can effectively promote the recovery of motor function, improve ADL, and enhance psychological status in stroke patients. However, due to the limited number of long-term studies with rigorous intervention protocols, the current analysis of the mechanisms underlying the improvement of physical and mental health in CVA patients through VR training lacks persuasive power